"Nobody views it as a negative thing to smoke": A qualitative study of the relationship between United States Air Force culture and tobacco use. Issue 6 (2nd November 2021) - Krukowski, Rebecca A.; Porter, Kathleen; Boothe, Tina; Talcott, G. Wayne; Little, Melissa A.
ABSTRACT: Tobacco use has long been a part of military culture, and rates of tobacco use remain higher among military personnel compared to civilians. The current study examines aspects of Air Force tobacco culture that encourage tobacco use. We conducted seven focus groups among Air Force Military Training Leaders (n = 48) and five focus groups among Technical Training Instructors (n = 33) from July 2018 to February 2019. Tobacco use was seen as a core part of Air Force culture and a low-risk behavior, in contrast to other potential activities. Three themes of Air Force culture that facilitate tobacco use emerged: 1) opportunity for work breaks; 2) finding common ground; and 3) stress management or stress relief during deployment. Smoke pits were seen as serving several functions that were not perceived to occur anywhere else: an opportunity for informal communication with leadership, a source of valuable information, and a space for problem-solving. Airmen viewed tobacco as serving a functional role, which outweighed its harm. Future programs might try to address the functions fulfilled by tobacco in order to enhance their impact.